Sustainability in small urban complexes - Halgourd , Rasouli Dehbokri (2008)
After the second war and re-habitation of destroyed places, the cooperation of modern environmental designer and architects glorified urban construction and urban issue as an important urban construction and architectural one. Building new cities by prepared design of neighborhood units and determination of parishes have been carried out by an individual or a special group for thousands of people. Stability of cities and their re-habitation are important matters for architects and designers of 21thcentery. The main view of designers about environmental psychology for finding dynamic trend and stability of public spaces in quarter scale are investigated attention to requirements in daily communication with neighbors, passengers and other users in good environment, perish centers, markets and public space is considered in small urban complex. These issues are proposed by psychologist and architects of 60th and 70th decades in late 20th century in environmental psychology frame. John Lang, Christian Norberg Schultz, Christopher Alexander, etc… are successful architects in this field. Their works are comprehensive references.